Chemical Content of Sidempuan Salacca (Salacca sumatrana) Vinegar and Its Potential as an Antihypercholesterolemia: an in Vitro Assessment - Atifah, Yusni; Ahda, Yuni; Parbuntari, Hesty; Lubis, Jalilah; Kurnia, Aifa; Ghina, Mutiara (Science & Technology Asia, 2025)
Sidempuan salacca (Salacca sumatrana Becc.) is a snakefruit native to Padangsidempuan, South Tapanuli, North Sumatra, Indonesia, known for its sweet-sour taste. Its sourness reduces market appeal and causes economic losses for farmers, while its perishable nature limits shelf life. To enhance its marketability, processing it into vinegar offers a promising alternative, as salacca vinegar has greater functional potential than apple vinegar. This study aimed to identify the chemical composition of Sidempuan salacca vinegar using GC-MS analysis and evaluate its antihypercholesterolemic potential. GC-MS results revealed five dominant bioactive compounds: oleic acid, DI-(9-octadecenoyl)-glycerol 2-hydroxy-1,3-propanediyl ester, borane, 9-octadecenal, and 9-octadecenoic acid (Z). An in vitro cholesterol-lowering assay using the Liebermann–Burchard method and spectrophotometry showed that the vinegar effectively reduced cholesterol, with an LC50 value of 142.232 ppm. In conclusion, Sidempuan salacca vinegar contains active compounds with antioxidant and anti-cholesterol properties, demonstrating potential as a natural functional product for managing cholesterol levels.